Spectaflavoside A, a new potent iron chelating dimeric flavonol glycoside from the rhizomes of Zingiber spectabile Griff - Leong, K.H. (Elsevier, 2012)
The rhizomes of Zingiber spectabile yielded a new dimeric flavonol glycoside for which the name kaempferol-3-O-(4″-O-acetyl)-α-l-rhamnopyranoside-(I-6,II-8)-kaempferol-3-O-(4″-O-acetyl)-α-l-rhamnopyranoside; spectaflavoside A (1) was proposed, along with kaempferol and its four acetylrhamnosides (2–6), demethoxycurcumin (7) and curcumin (8). The structure of spectaflavoside A was elucidated by spectroscopic methods including, 1D and 2D NMR techniques. This is the first report on the occurrence of a dimeric flavonol glycoside in the Zingiberaceae and the second in nature. Spectaflavoside A was found to be a potent iron chelating agent.